(untitled) - Fellows, Richard (Chichester, 2015)
Research Methods in Construction will help you instil rigour into your problem-solving, and into your reports and publications. It will be of value to construction, surveying, architecture and civil engineering students undertaking research, whether for bachelors and masters degree dissertations, or for masters and doctoral research degree theses. Now in its Fourth Edition, this remains one of the few books to provide guidance on research formulation, methodologies, and methods specifically for construction students.
Keywords: Xây dựng,Building; Nghiên cứu,Phương pháp dạy,Research,Methodology